Time-reversal symmetry broken quantum spin Hall phase in the van der Waals heterostructure ZrTe5/Cr2Ge2Te6. (1st September 2022) - Xiao, Xiaoliang; Zhan, Fangyang; Kong, Weixiang; Fan, Jing; Wang, Rui; Wu, Xiaozhi
Abstract: The topological phases with time-reversal symmetry (TRS) breaking have always attracted intense studies due to their potential applications to spintronics. The previous studies mainly focused on the exploration of quantum anomalous Hall effects, but another typical TRS-broken two-dimensional topological phase, i.e., the TRS-broken quantum spin Hall (QSH) effect, has rarely been proposed in realistic materials. Here, based on first-principles calculations and topology analysis, we show that the van der Waals heterostructure ZrTe5 /Cr2 Ge2 Te6 can realize the robust TRS-broken QSH state. We utilize the topological edge states and spin Hall conductance, which can be measured in experiments directly, to confirm the appearance of TRS-broken QSH phase. Moreover, we uncover that the built-in electric field is essential to realize such topological state and an external electric field can effectively tune the nontrivial band gap. Our findings not only provide a reliable candidate to obtain the TRS-broken QSH phase with a high tunability but also can facilitate further applications to topological quantum transport.